The Evolution of Breast Implants - Kaoutzanis, Christodoulos; Winocour, Julian; Unger, Jacob; Gabriel, Allen; Maxwell, G. Patrick (Seminars in Plastic Surgery, 2019)
Breast augmentation remains one of the most commonly performed aesthetic procedures in the United States and worldwide. Throughout the last few decades, the implants used for this procedure have undergone significant advancements, which has allowed surgeons to provide safer and more aesthetically pleasing outcomes. This article discusses the history of breast implants since their invention in 1962. Particular emphasis is given to the evolution of silicone implants with its many challenges, which has resulted in the development of the currently used fourth- and fifth-generation devices. Knowledge of these advances will allow physicians to more critically evaluate their results, and also will encourage them to provide more up-to-date scientific data on these devices to further improve the clinical outcomes of their patients.
Keywords: breast implant; silicone breast implant; evolution; aesthetic surgery; cosmetic surgery